Two-Dimensional kinematics of horses at trot through videometry and mathematical modeling - Torres-Pérez, Yolanda; Gómez-Pachón, Edwin Yesid; Miró-Rodriguez, Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Currently, the direct observation method is used to assess the movement of horses; however, this method is limited, totally subjective, and many details of the musculoskeletal system functionality cannot be detected and evaluated because they are not perceptible to the naked eye. This study aimed at developing a mathematical model that calculates, plots, and simulates the 2D angular movement of some horse joints. The horse musculoskeletal system was modeled as a mechanical system of rigid bodies articulated by 15 simple joints. The mathematical solution of the mechanism was obtained from the standpoint of inverse kinematics (flat) liabilities. We constructed 15 link equations, associating the body segments of the system in movement with an inertia base, and used the mathematical optimization method based on the least squares calculation. We obtained kinematic curves of the main joints, as well as the trajectories (height) of the markers on fore and hind coronary band (hoofs), and a simulation of the mechanical system. This tool removes subjectivity and enables veterinarians to observe, evaluate (qualitatively and quantitatively), diagnose, and investigate different phenomena of the horse gait.